The Charter of the City of Newport, R. I., and the Special State Laws Relating Thereto, Together with the Ordinances for the Government of the City, at 39, An Act providing in case of fire breaking out in the town of Newport an for the purposes therein mentioned, § 11 (1858) - (:unkn) unknown (General Publisher, 1822)
That no person whosoever shall fire a gun or other fire-works within one hundred yards of the said powder-house, upon the penalty of two dollars for every such offence, to be recovered by the town treasurer for the use of said town.
--
Keywords: DISCHARGE